2010
DOI: 10.1007/s12026-009-8136-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in antibody- and complement-mediated allograft rejection

Abstract: Antibody-mediated rejection has become critical clinically because this form of rejection is usually unresponsive to conventional anti-rejection therapy, and therefore, it has been recognized as a major cause of allograft loss. Our group developed experimental animal models of vascularized organ transplantation to study pathogenesis of antibody- and complement-mediated endothelial cell injury leading to graft rejection. In this review, we discuss mechanisms of antibody-mediated graft rejection resulting from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 146 publications
1
45
0
Order By: Relevance
“…180 -182 There are 3 major pathways of complement activation: classical, alternative, and mannosebinding lectin (MBL)-dependent pathways. 181,183 The classical pathway is thought to be triggered by binding of immunoglobulin immunoglobulin M (IgM; and certain classes of immunoglobulin G [IgG]) to the foreign antigens), whereas the alternative and MBL-dependent pathways involve recognition of foreign surfaces and binding of MBL to foreign microbes, respectively. 181,183 Despite the difference in the initiating factors, all 3 pathways share the central process of complement component C3 activation, which can lead to the generation of (1i) C3a and C5a, which can act as inflammatory mediators, (2) C3b can mediate the opsonisation and engulfment of foreign material by phagocytes, and ultimately, (3) terminal complement components that together form the C5b-9 membrane attack complex can trigger subsequent damage and destruction of the targeted (foreign) cells, eg, myocytes of the cardiac allograft.…”
Section: Complement and (Allo)antibodies Participate In Rejection-relmentioning
confidence: 99%
See 1 more Smart Citation
“…180 -182 There are 3 major pathways of complement activation: classical, alternative, and mannosebinding lectin (MBL)-dependent pathways. 181,183 The classical pathway is thought to be triggered by binding of immunoglobulin immunoglobulin M (IgM; and certain classes of immunoglobulin G [IgG]) to the foreign antigens), whereas the alternative and MBL-dependent pathways involve recognition of foreign surfaces and binding of MBL to foreign microbes, respectively. 181,183 Despite the difference in the initiating factors, all 3 pathways share the central process of complement component C3 activation, which can lead to the generation of (1i) C3a and C5a, which can act as inflammatory mediators, (2) C3b can mediate the opsonisation and engulfment of foreign material by phagocytes, and ultimately, (3) terminal complement components that together form the C5b-9 membrane attack complex can trigger subsequent damage and destruction of the targeted (foreign) cells, eg, myocytes of the cardiac allograft.…”
Section: Complement and (Allo)antibodies Participate In Rejection-relmentioning
confidence: 99%
“…181,183 Despite the difference in the initiating factors, all 3 pathways share the central process of complement component C3 activation, which can lead to the generation of (1i) C3a and C5a, which can act as inflammatory mediators, (2) C3b can mediate the opsonisation and engulfment of foreign material by phagocytes, and ultimately, (3) terminal complement components that together form the C5b-9 membrane attack complex can trigger subsequent damage and destruction of the targeted (foreign) cells, eg, myocytes of the cardiac allograft. 181,183,184 …”
Section: Complement and (Allo)antibodies Participate In Rejection-relmentioning
confidence: 99%
“…Unwarranted macrophage activation and infiltration of tissues has been implicated in a number of diseases, including diabetes, rheumatoid arthritis (RA), organ transplant rejection, atherosclerosis and cancer progression (Cookson, 1971;Coussens and Werb, 2002;Davies et al, 2013;Lech et al, 2012;Mantovani et al, 2013;Sebbag et al, 1997;Steinman and Cohn, 1973;Wasowska, 2010;Weisberg et al, 2003;Xu et al, 2003). Macrophages are capable of both amoeboid and mesenchymal migratory phenotypes (Van Goethem et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperacute rejection occurs within minutes to hours of the blood flow being reestablished and is caused by preformed antibodies to ABO blood group antigens, HLA, or endothelial antigens. Antibodies in the blood of the recipient bind to the vascular endothelium of the transplant and activate complement, which results in neutrophil infiltration, vascular disruption, hemorrhage, fibrin deposition and platelet aggregation [10]. It is rare owing to tests for DSAs [11].…”
Section: Acute Antibody-mediated Rejectionmentioning
confidence: 99%
“…According to published data [24,25] it is most probable that MBL correlates positively with C4d deposition. Wasowska et al [10] suggested combine mechanism of MBL depending on both complement-activating and non-activating antibodies. Nonetheless, further studies are needed within this pathway.…”
Section: Acute Antibody-mediated Rejectionmentioning
confidence: 99%